Investigating the best mixture extraction systems in the separation of rare earth elements from nitric acid solution using Cyanex272, D2EHPA, and 8-Hydroxyquinoline. Issue 1 (2nd January 2016) - Seyed Alizadeh Ganji, Seyed Mohammad; Shafaei, Seied Ziaeddin; Goudarzi, Nasser; Azizi, Asghar
Abstract: This study is aimed at determining the optimum mixing ratio and solvent group to extract REEs from nitric leach solution, and the efficiency was tested using three different kinds of extractants, which were prepared to mix three different solvents of Cyanex272, D2EHPA, and HQ. In order to select the best mixture system, different volumes (ml) of solvent extractions were used under optimum conditions (.05 M concentration and pH of 2). The result indicated that the mixture system of Cyanex272 (8 ml) and D2EHPA (2 ml) had the highest separation factor and enrichment ratio in the separation of rare earth element, especially dysprosium. The degree of performance of mixture systems in separation of the rare earth elements indicated that the best extraction systems were in the order of Cyanex272 (8 ml) and D2EHPA (2 ml) > HQ (2 ml) and D2EHPA (8 ml) > Cyanex272 (8 ml) and HQ (2 ml).